Optimal energy management of solar-assisted heat pump water heating systems: a case of student residences at the Central University of Technology, Free State - Gaonwe, Tsholofelo Priscilla (Central University of Technology, 2022)
In South Africa, more than 40% of the energy produced, is estimated to be consumed in the commercial sector. Organizations, such as universities in South Africa, are faced with increased pressure to manage energy demands and escalating energy costs. This has resulted in the country currently facing ambiguous tariff increases, at short intervals, by the power utilities and rolling blackouts that could possibly lead to a grid shutdown. On the other hand, most institutions were not designed to be energy efficient, as they were mostly constructed in an era when energy optimization did not offer sufficient financial benefits. Therefore, energy efficiency is seldom viewed as a core university function. Standard electric storage tank-water heaters (ESTWHs) are the most used systems for sanitary water heating and are a major contributor to the undesirable high morning and afternoon peaks in energy demand. Another reason is that these systems rely solely on thermostat systems for operation control, with no other energy management activities (or technologies) in place. In addition, the thermostat automatically switches ON/OFF, to heat water to the end user’s set desired thermal level throughout the day, whenever the temperature drops below the set point, due to standby losses. All these things, therefore, add to the cost of the monthly bills of the users. Using renewable energy source water heating systems, such as air-source heat pump water heaters (ASHPWHs) and solar water heaters (SWHs), may further assist to reduce excessive energy demand and the cost of hot water production. However, these standalone water heating systems are insufficient, in the case of a great deal of hot water production whereby continuous energy supply is needed. This is due to the slow heating processes of the ASHPWHs and SWHs being solely dependent on thermal heat from the sun to heat the water. Furthermore, like the ESTWHs, the electricity-driven HP units on the market use primary thermostat control systems, which may further contribute to the energy consumption during the peak period. Solar-assisted heat pump water heaters (SAHPWHs), are a possible solution to the escalating electricity charges, faced by the South African community, particularly for the continuous demand for sanitary hot water in the commercial sector, such as university student residences. The solar system may provide a great amount of thermal energy to supply the heat pump unit during the time when the sun is available, while the heat pump consumes a minimal amount of energy, during the time when there is minimal to no solar energy available, to heat the water. These SAHPWH technologies may be a solution to assist with reducing the high energy demand, which will further help alleviate the pressure on the electricity supply grid. Additionally, implementing an optimal energy control scheme, to load shifting by the TOU tariff plan, may help alleviate demand strain on the supply grid, as well as optimize energy savings, while maintaining the consumer’s thermal comfort level. In this study, an IDX-SAHPWH system, operating under an optimal energy control scheme, integrated with the load shifting by TOU pricing plan, is proposed for the commercial sector. A student residence was used as a case study. A mathematical model of the proposed system was developed, and the optimal operation control problems were formulated. The Solving Constraint Integer Programs (SCIP) solver, in the MATLAB interface optimization toolbox, was used for the simulations, with the considered computational variables taken at 20-minute intervals. The baseline model was further simulated using the same component sizing, as well as under the same climate conditions. From the simulation results, the proposed system, under the optimal energy control scheme integrated with the load shifting by TOU pricing plan, operates optimally, as it avoids the peak and standard periods of the TOU tariffs, which guarantees savings in energy and costs, as compared to the baseline ESTWH. The proposed system ensures that water is heated during the off-peak period to the highest temperature that will be able to maintain the thermal level of the consumers, throughout the high TOU tariff periods. The techno-economic analysis of the optimally controlled proposed system and the baseline systems were conducted and presented for a project lifespan of 20 years. All cost aspects were considered in the analysis and, from the results obtained, the IDX-SAHPWH system showed significant savings. The cost savings obtained from the winter and summer seasons, as well as annual, are 76.0 %, 75.6 % and 75.8 %, respectively. The break-even point of the project is during the 9th month of the first year of the project, with a possible savings of 71.5 % at the end of the project's lifetime. It may therefore be concluded that the aim of this study has been met as the IDXSAHPWH system, when operated with the optimal energy control scheme, integrated with the load shifting by TOU pricing plan, shows a very significant savings in costs, which maintaining the thermal comfort level of the consumers. Furthermore, the system may contribute to the load reduction during peak energy usage periods on the electricity grid supply. As a result, this system can be used in any commercial enterprise, that has a high demand for sanitary water heating.
Thesis (Master: Engineering: Mechanical Engineering)--Central University of Technology
Keywords: Energy optimization; Renewable energy source water heating systems; Solar-assisted heat pump water heaters